Discussion - Of the Paper by a Sub-committee of the American Society for Testing Materials on Standard Specifications for Pig-Iron and Iron Products (see p. 162) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
AlbioN S. Howe, San Francisco, Cal. (communication to the Secretary*):—In discussing this paper, 'I mould suggest that. the dip for iron pipe be liquid asphaltum, instead of coal-tar and pitch. Asphaltum is superior to coal-tar, and the variety